2013
DOI: 10.1530/rep-13-0173
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific differences in X chromosome inactivation in mammals

Abstract: In female mammals, the dosage difference in X-linked genes between XX females and XY males is compensated for by inactivating one of the two X chromosomes during early development. Since the discovery of the X inactive-specific transcript (XIST) gene in humans and its subsequent isolation of the mouse homolog, Xist, in the early 1990s, the molecular basis of X chromosome inactivation (X-inactivation) has been more fully elucidated using genetically manipulated mouse embryos and embryonic stem cells. Studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 80 publications
2
23
0
Order By: Relevance
“…Previously, Sado and Sakaguchi proposed that chromatin condensation states in parental genomes differed in each specie and that this might define imprinted XCI [34]. In the current study, we showed that the asymmetric chromatin condensation states of parental Xist / Tsix genomic regions are crucial for the initiation of Xist expression in mice (Fig 7b).…”
Section: Discussionsupporting
confidence: 68%
“…Previously, Sado and Sakaguchi proposed that chromatin condensation states in parental genomes differed in each specie and that this might define imprinted XCI [34]. In the current study, we showed that the asymmetric chromatin condensation states of parental Xist / Tsix genomic regions are crucial for the initiation of Xist expression in mice (Fig 7b).…”
Section: Discussionsupporting
confidence: 68%
“…Although early studies suggest that the choice for which X-chromosome is inactivated is random (43), later studies on female carriers of specific X-linked mutations showed skewed patterns of XCI resulting from negative selection of cells harboring the lethal allele in the active state (44). Furthermore, X-chromosome skewing is a common feature of tumorigenic processes in which an acquired somatic mutation occurs in a single progenitor cell that subsequently undergoes clonal expansion and gives rise to progeny with the same XCI pattern (44, 45). …”
Section: Resultsmentioning
confidence: 99%
“…If the chromatin structure of the maternal Xist locus needs further cell division to become similar to that of the paternal locus, this would account for the lag in the timing of maternal Xist CAG being upregulated relative to paternal Xist CAG . Such a difference in the chromatin structure, if any, may also be relevant to the monoallelic upregulation of Xist in wild-type female embryos in favor of the paternal allele during preimplantation development (Sado and Sakaguchi, 2013). In other words, the maternal Xist allele was repressed during early cleavage stages because it was not yet ready for transcription owing to the compact chromatin structure being inaccessible by transcription factors.…”
Section: Discussionmentioning
confidence: 99%